Front Cover: Institute Feature: IOCB Prague (Eur. J. Org. Chem. 37/2018). Issue 37 (12th September 2018) - Hocek, Michal; Hostomský, Zdeněk
Abstract : The Front Cover shows the newly constructed organic synthesis building of the Institute of Organic Chemistry and Biochemistry of the Czech Academy of Sciences (IOCB) in Prague. Featuring at the front are examples of molecules that are showcased in this collection of papers from researchers of the IOCB. More information on the institute and the research performed there can be found in theGuest Editorial by Z. Hostomský of the special issue "Institute Feature: IOCB."